NILAI-NILAI KARAKTER DALAM PEMBELAJARAN APRESIASI SENI BERBASIS MULTIKULTURAL - Sugiarto, Eko (Sabda: Jurnal Kajian Kebudayaan, 2013)
Cultural values in accordance with the substance a/education which is to educate the nation as a whole, have changed direction into a value-and-job oriented human beings. Going to school or college, a person is only to get the predicate of "pass" with apiece of evident "certificate", instead of becoming an educated intelligent man intellectually, emotionally, and spiritually. Such reality raises various concerns among education observers. Indonesia is gradually losing its national character. The issue of national character is a question of culture. Therefore, the character education should also be multiculturally based, -which is implicitly inherent in "learning about the arts ", "learning the arts ", and "learning through the arts ". Art education has a strategic position, so it has the potential to implement the national character education. The development of the implementation of art education leading more greatly to multicultural-based character value that requires conceptual contribution of all parties is needed. In general this paper discusses the implementation of art learning in order to manifest multicultural-based character education as a response to the road map for arts-education, Unesco.